Kinetic Models of Trymethylolpropane (TMP) and Castor Oil Methyl Ester Transesterification for engine oil synthesis - Said, N.; M. V., Sivaguru; Mohd Sabri, Mahmud; H. A. M., Sukri; F. H., Ahmad; S. A., Khairuddin (2018)
Non-digestible oil as renewable resources has grown a compulsive concern for engine oil synthesis. The synthesis of engine oil was conducted in a bath stirrer flask via two-steps catalytic transesterification. Modification of trimethylolpropane (TMP) and castor oil methyl ester (COME) transesterification was run under non- and impregnated Perna V. shells catalysts. Operation temperature effect on the castor trimethylol propane triester as engine lubricant was conditioned at range 90°C – 130°C. The optimal reaction temperature was detected at 110°C with 98.60 % TMP conversion and 71.29% triester composition. Excess dosage of COME was structured at 4:1 ratio to TMP for progressive reaction limitation. Kinetics of TMP and COME transesterifation were established for first- and second orders. The second order kinetic model best matchs the acquired data for an overall reaction rate constants of 0.0354 (% wt/wt min °C)-1. Synthesized engine oil resulted activation energy of 74.10 kJ/mol. Estimated pour and flash point were -17 °C and 221°C. Kinematic viscosity at 40°C was 64.31 mm2/s and density was 872 kg/m3 fulfilled the proposed lubricant standard. The kinetic models were proportionate to other oil seeds crops based engine oil, typically Jatropha seeds oil.